Figures 46-49 from: Prous M, Vikberg V, Liston A, Kramp K (2016) North-Western Palaearctic species of the Pristiphora ruficornis group (Hymenoptera, Tenthredinidae). Journal of Hymenoptera Research 51: 1-54. https://doi.org/10.3897/jhr.51.9162 - Prous, Marko; Vikberg, Veli; Liston, Andrew; Kramp, Katja (Zenodo, 2016)
Figures 46-49 - Lancets of Pristiphora melanocarpa showing variation in the shape of the tangium. Some of the specimens have rather distinct small outgrowth between tangium and laminum (arrow in Fig. 49). 46 PR.436VV reared ex larva from Betula pubescens 47 PR.423VV reared ex larva from Betula pubescens 48 PR.434VV 49 PR.431VV, several larvae were reared ex ovo from this female ovipositing in the leaves of Betula nana.